Evaluation of critical shattering time of early-maturity soybeans under early soybean production system - Zhang, L.; Boahen, S. (2010)
One of the major problems associated with the early soybean production system (ESPS) in the Midsouth USA is seed shattering of early maturity group (MG) soybean that mature in the midsummer. Information is needed to measure the impact of this problem and to provide proper management strategies. Studies were conducted to investigate the problem of shattering in MG IV soybean, the dominant soybean group in ESPS, in 2006 and 2007. The objectives of this study were to determine the pattern and critical period of seed shattering of MG IV soybeans under various climatic and production conditions in the Mississippi Delta. A total of 56 and 80 MG IV soybean varieties were evaluated in the experiments in 2006 and 2007, respectively. The varieties were all selected from a Mississippi Soybean Variety Trial and the study was carried out at Stoneville Mississippi. In 2006, only the April planting (April 19) under irrigation was investigated. In 2007, experiments were conducted on both irrigated and non-irrigated fields. On the irrigated tests, both April (April 23) and May (May 15) planting were examined. Results from both years have indicated that most pods of early MG IV soybean varieties can hold seeds relatively well for the first three weeks after maturity (WAM). However, differences were noted starting from the fourth WAM. Non-irrigated soybean shattered faster than irrigated soybean after three weeks. Irrigated soybean held seeds longer than non-irrigated soybean during the fourth week; however, seed shattering became greater after four weeks even in the irrigated study. When comparing early- and late-planted soybean under irrigated conditions, the later maturing pods held seeds better within the same period after maturity (up to 6 weeks or longer). Late-maturing pods tended to held seed better, most likely due to lower temperatures experienced after late September.